The effect of a physical wellness pathway on the chronic absenteeism of shift workers at an Eskom power station - Schouw, Darcelle D. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScSportSc)--University of Stellenbosch, 2003.